Obesity and cancer - Pischon, Tobias; Nimptsch, Katharina (Recent results in cancer research, 2016)
This book provides a comprehensive and up-to-date review of the relationship between obesity and cancer. It opens with a global perspective on obesity and cancer incidence, followed by in-depth discussions of those cancers for which we have sufficient evidence of a causal relationship with obesity. It addresses topics such as the effects of obesity on cancer incidence and cancer survival, the effects of weight gain and weight loss in adulthood on cancer risk, the effects of childhood and adolescent obesity, and the role of body fat distribution in cancer risk. Individual chapters discuss potential pathways for the observed associations and explore possible mechanisms from both an epidemiological and an experimental perspective. It concludes with a population perspective on the cancer risk that is attributable to obesity and is thus potentially avoidable. This book is of particular value to researchers and epidemiologists and is also of interest to public health workers and clinicians